Roles of small RNAs in soybean defense against Phytophthora sojae infection - Wong, James (Plant J, 2014)
The genus Phytophthora consists of many notorious pathogens of crops and forestry trees. At present, battling Phytophthora diseases is challenging due to a lack of understanding of their pathogenesis. We investigated the role of small RNAs in regulating soybean defense in response to infection by Phytophthora sojae, the second most destructive pathogen of soybean. Small RNAs, including microRNAs (miRNAs) and small interfering RNAs (siRNAs), are universal regulators that repress target gene expression in eukaryotes. We identified known and novel small RNAs that differentially accumulated during P. sojae infection in soybean roots. Among them, miR393 and miR166 were induced by heat-inactivated P. sojae hyphae, indicating that they may be involved in soybean basal defense. Indeed, knocking down the level of mature miR393 led to enhanced susceptibility of soybean to P. sojae; furthermore, the expression of isoflavonoid biosynthetic genes was drastically reduced in miR393 knockdown roots. These data suggest that miR393 promotes soybean defense against P. sojae. In addition to miRNAs, P. sojae infection also resulted in increased accumulation of phased siRNAs (phasiRNAs) that are predominantly generated from canonical resistance genes encoding nucleotide binding-leucine rich repeat proteins and genes encoding pentatricopeptide repeat-containing proteins. This work identifies specific miRNAs and phasiRNAs that regulate defense-associated genes in soybean during Phytophthora infection.